Work Stress on Employees of Perum BULOG Bulukumba Branch - Muhammad Darwis; Syahruni; Sitti Hardiyanti Arhas; Tunggul Prasodjo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
Perum BULOG Bulukumba Branch has a big responsibility in achieving marketing targets and distributing commodities, especially in the Bulukumba area. This study aims to find out how work stress is on employees and what are the determinants of work stress on employees of Perum BULOG Bulukumba Branch. To achieve this goal, the researchers used data collection techniques, namely observation, interview, and documentation techniques. The informants in this study were SCPP assistant manager, 2 SCPP staff, 1 accounting staff, 1 administrative and financial staff, and 1 business staff. Data analysis techniques used in this study are data reduction techniques, data presentation, conclusions, and verification. The results showed that work stress on employees of Perum BULOG Bulukumba Branch arises because of the lack of employees so that the workload of employees becomes greater, besides that slow internet connections and inadequate office facilities hinder employee work processes, causing work stress on employees. This research can be used as a source of information and knowledge about work stress in employees in more depth because it is different from previous studies which mostly use quantitative methods that focus on numbers and statistics, this study uses qualitative methods that produce hypotheses and more detailed descriptions of work stress on employees. In addition, a slow internet connection and inadequate office facilities hinder employee work processes, causing work stress for employees. This research can be used as a source of information and knowledge about work stress in employees in more depth because it is different from previous studies which mostly use quantitative methods that focus on numbers and statistics, this study uses qualitative methods that produce hypotheses and more detailed descriptions of work stress on employees. In addition, a slow internet connection and inadequate office facilities hinder employee work processes, causing work stress for employees. This research can be used as a source of information and knowledge about work stress in employees in more depth because it is different from previous studies which mostly use quantitative methods that focus on numbers and statistics, this study uses qualitative methods that produce hypotheses and more detailed descriptions of work stress on employees.